Among poets we are: Noces (Camus) and Cántico (Guillén) - Víquez Jiménez, Alí (2019)
This essay develops a comparison between the texts “Noces” (Albert Camus) and “Cántico” (Jorge Guillén). Its objective is to deepen the aesthetic and ph1ilosophical approach that both authors make about the state of human happiness and its celebration by means of the poetical word. By contrasting the texts, the paper reaches conclusions about the assessment of the present, that has points in common in both writers, and establishes the differences with which the assessments are made. Key Words: French literature, Spanish literature, Comparative literature, Contemporary European literature, Spanish poetry.